2004
DOI: 10.1021/jp031308q
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Boron and Related Systems:  An ab Initio Study of B−X and YB⋮BY (1Σg+), Where X = He, Ne, Ar, Kr, CO, CS, N2 and Y = Ar, Kr, CO, CS, N2

Abstract: Using the coupled-cluster methodology and large correlation consistent basis sets, we have examined the BX and YBBY (1Σg +) molecules, where X = He, Ne, Ar, Kr, CO, CS, and N2 and Y = Ar, Kr, CO, CS, and N2. For the B−X series we have constructed full potential energy curves reporting total energies, equilibrium geometries, binding energies, and also spectroscopic constants for the diatomic sequence. The B−CO, B−CS, and B−N2 ground states are of 4Σ- and 2Π symmetries, respectively, with the 4Σ- states having r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 21 publications
7
44
0
6
Order By: Relevance
“…It is noteworthy that, although the electronegativity of the C, O and N atoms is higher than that of the B atom, and the electrons should transfer from BB to ∶CO and ∶NN, the electrons shift conversely, perhaps due to that these substituents have lone-pair electrons and the boron atom is electron-deficient. Thus, the substituents might offer the lone-pair electrons to the electron-deficient boron atom, as is in accordance with the investigation by Papakondylis et al [12].…”
Section: Apt Atomic Chargesupporting
confidence: 90%
See 3 more Smart Citations
“…It is noteworthy that, although the electronegativity of the C, O and N atoms is higher than that of the B atom, and the electrons should transfer from BB to ∶CO and ∶NN, the electrons shift conversely, perhaps due to that these substituents have lone-pair electrons and the boron atom is electron-deficient. Thus, the substituents might offer the lone-pair electrons to the electron-deficient boron atom, as is in accordance with the investigation by Papakondylis et al [12].…”
Section: Apt Atomic Chargesupporting
confidence: 90%
“…Recently we have found that the investigation on the monomer and T-shaped X-H…π hydrogen-bonded complex involving the BB multiplebond has always been of the interesting topic, accompanied by the unusual "phenomenon" [11][12][13]. For example, the electron-deficient BB bond in LBBL shows the double-bond and triple-bond characteristic with the single-electron donating/withdrawing (L = −H, -CN, -F, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2À in der Gasphase, das einen berechneten B-B-Abstand zwischen 1.481 und 1.504 aufweist. [43] Diese Berichte wurden von theoretischen Studien der Gruppen von Mavridis [44] und Frenking [43b] begleitet, die eine Reihe von Donoren wie Edelgasatome, CO, CS und N 2 zur Stabilisierung der B 2 -Einheit untersuchten und diese kurzen B-B-Abstände bestä-tigten.…”
Section: Neuere Arbeitenunclassified